The Effect of Autologous Platelet Rich Plasma on Endometrial Receptivity: A Narrative Review - Milan Stefanović; Predrag Vukomanović; Ranko Kutlesic; Milan Trenkić; Vanja Dimitrov; Aleksa Stefanović; Vladimir Cvetanović (Medicina)
Background and Objectives: Autologous platelet-rich plasma (PRP) transfusions are a relatively new treatment method used in different fields of medicine, including the field of reproductive medicine. One of the applications of these concentrated platelet infusions is the treatment of endometrial receptivity, which is a key factor for embryo implantation. There are implications that PRP infusions can lead to increased endometrial thickness, endometrial receptivity, and significantly elevated clinical pregnancy rates. Our objective is to briefly understand what PRP is and to, through a narrative review, summarize the findings from studies focused on evaluating the benefits of PRP infusions to treat thin endometrium with the goal of achieving better endometrial receptivity. Materials and Methods: Reference data was searched using Medline, PubMed, and EMBASE to identify reports from 2015 to 2024. The combination of search words used was “PRP” and “platelet-rich plasma” with “thin endometrium”, “endometrial receptivity”, “endometrial thickness”, and “endometrial implantation”. Obtained articles were screened, and suited studies (randomized controlled trials, case reports, case series, pilot studies, and reviews) were included in the present review. Reports not available in the English language were eliminated from the current review. Results: The results from most of the reviewed studies showed a positive effect of autologous PRP infusions on increasing endometrial thickness, enhancing endometrial receptivity, and elevating clinical pregnancy rates. The majority of the evaluated findings revealed endometrial thickness > 7 mm (increased endometrial thickness was observed in each evaluated study) following the PRP treatment. More than 50% of the evaluated studies resulted in enhanced endometrial thickness, increased endometrial receptivity, and an elevated pregnancy rate after the PRP application. Conclusions: Autologous PRP infusions for treating endometrium are a relatively new method that has shown promising results. Its major strengths are availability and proper application, which eliminates possible immunological reactions or disease transmission. The main drawbacks are not enough data on safety (i.e., its effect on endometriosis) and the lack of uniformity in the PRP preparation, which would provide optimal standardized quality and quantity of the PRP product and, thus, optimal treatment results.